2015
DOI: 10.1177/1535370215570189
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormone affects the severity of non-alcoholic steatohepatitis through the MyD88-dependent IL-6 signaling pathway

Abstract: Recent research has shown that the occurrence of gender disparity in liver cancer associated with sex differences in MyD88-dependent IL-6 production, but the role of this signaling pathway in sex differences of non-alcoholic steatohepatitis (NASH) remains unknown. To investigate the effects of sex hormone-specific intervention on pathology and progression of NASH, and on the inflammatory TLR-MyD88-IL-6 signaling pathway NASH was modeled in C57/BL6 mice by feeding a methionine and choline-deficient (MCD) diet f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
16
1
1
Order By: Relevance
“…S4). The levels that we recorded were similar to those previously published by others for male (testosterone) and female (estradiol) mice (22,23). Our results do not support obvious hormonal modifications as a mechanism by which gestational BPA increases EAE susceptibility in adult male mice.…”
Section: Gestational Bpa Exposure Alters Responses Of Macrophages Culsupporting
confidence: 79%
“…S4). The levels that we recorded were similar to those previously published by others for male (testosterone) and female (estradiol) mice (22,23). Our results do not support obvious hormonal modifications as a mechanism by which gestational BPA increases EAE susceptibility in adult male mice.…”
Section: Gestational Bpa Exposure Alters Responses Of Macrophages Culsupporting
confidence: 79%
“…Splenic artery resistive index (index of organ damage) overlapped between patients with NASH and those with fatty livers, but showed a difference to controls, pointing out that NASH patients did not present increased liver injury (followed by fibrosis and eventual portal hypertension) compared to fatty liver patients [29]. With regards to IL-6, most interestingly, recent results showed that different sex hormone-related interventions affected the severity of NASH, likely by impacting on the level of sex hormones and modulating the Toll-Like Receptor-MyD88-IL-6 signalling pathway, clearly reinforcing the hypothesis that IL-6 plays a key role in worsening the simpler fatty liver disease [30]. Finally, in a large, multi-ethnic population with NAFLD, IL-6 was independently associated with the prevalence and severity of subclinical atherosclerosis [31].…”
Section: Spleenmentioning
confidence: 68%
“…Plasma IL-6 values were increased in NASH patients in a pilot study [31]. Recent studies indicated that IL-6 contributed to the development of NAFLD [32,33]. IL-6 has also been demonstrated to play a pivotal role in the dichotomous differentiation programmes of Th17.…”
Section: Discussionmentioning
confidence: 99%